Distinct Amino Acids in the C-Linker Domain of the Arabidopsis K+ Channel KAT2 Determine Its Subcellular Localization and Activity at the Plasma Membrane . Issue 3 (9th January 2014) - Nieves-Cordones, Manuel; Chavanieu, Alain; Jeanguenin, Linda; Alcon, Carine; Szponarski, Wojciech; Estaran, Sebastien; Chérel, Isabelle; Zimmermann, Sabine; Sentenac, Hervé; Gaillard, Isabelle
Abstract : The C-linker domain of a K + channel is required for the control of channel gating via its first α-helix located just below the channel pore and for the proper folding of the channel . Abstract: Shaker K + channels form the major K + conductance of the plasma membrane in plants. They are composed of four subunits arranged around a central ion-conducting pore. The intracellular carboxy-terminal region of each subunit contains several regulatory elements, including a C-linker region and a cyclic nucleotide-binding domain (CNBD ). The C-linker is the first domain present downstream of the sixth transmembrane segment and connects the CNBD to the transmembrane core. With the aim of identifying the role of the C-linker in the Shaker channel properties, we performed subdomain swapping between the C-linker of two Arabidopsis ( Arabidopsis thaliana ) Shaker subunits, K + channel in Arabidopsis thaliana 2 (KAT2) and Arabidopsis thaliana K + rectifying channel1 (AtKC1). These two subunits contribute to K + transport in planta by forming heteromeric channels with other Shaker subunits. However, they display contrasting behavior when expressed in tobacco mesophyll protoplasts: KAT2 forms homotetrameric channels active at the plasma membrane, whereas AtKC1 is retained in the endoplasmic reticulum when expressed alone. The resulting chimeric/mutated constructs were analyzed for subcellular localization and functionally characterized. We identified two contiguous amino acids, valine-381 and serine-382, located in the C-linker carboxy-terminal end, which prevent KAT2 surface expression when mutated into the equivalent residues from AtKC1. Moreover, we demonstrated that the nine-amino acid stretch 312 TVRAASEFA320 that composes the first C-linker α-helix located just below the pore is a crucial determinant of KAT2 channel activity. A KAT2 C-linker/CNBD three-dimensional model, based on animal HCN (for Hyperpolarization-activated, cyclic nucleotide-gated K + ) channels as structure templates, has been built and used to discuss the role of the C-linker in plant Shaker inward channel structure and function.